2018
DOI: 10.1016/j.apenergy.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Charge-sensitive modelling of organic Rankine cycle power systems for off-design performance simulation

Abstract: True off-design models must be charge-sensitive to be fully deterministic. • To account for the charge helps to identify the heat exchangers coefficients. • Hugmark's void fraction model shows the best results to simulate two-phase flows. • The presence of a liquid receiver arises numerical issues to model ORC systems. • The charge-sensitive model is validated with experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 40 publications
(51 reference statements)
0
29
0
Order By: Relevance
“…Such detailed models are based upon the extensive literature available for vapor compression cooling and heat pumping systems [16,17]. A recent overview of off-design steady-state performance studies and modeling applied to ORC systems can be found in [8].…”
Section: Definition Of a Mechanistic Model For Orc Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Such detailed models are based upon the extensive literature available for vapor compression cooling and heat pumping systems [16,17]. A recent overview of off-design steady-state performance studies and modeling applied to ORC systems can be found in [8].…”
Section: Definition Of a Mechanistic Model For Orc Systemmentioning
confidence: 99%
“…Yet, very limited work can be found on the impact of working fluid charge on off-design operations. In fact, besides the research conducted by the Authors [6][7][8], only two additional studies could be found in the literature. Liu et al [9] discussed the effect of different working fluid charge masses on the system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding advances in simulations, Haervig et al [21] screened with a genetic optimization algorithm 26 common working fluids for a heat source in the temperature range of 50-280 • C. Critical conditions and the slope of the vapor line were found to be important criteria of optimization parameters for a given heat source temperature. Dickes et al [22] developed a charge-sensitive model of a 2 kWe recuperative ORC to characterize and optimize the performances of ORC for off-design operation. Regarding the available experimental studies screened thanks to the Landelle et al [23] database, two working fluids have been principally investigated in the corresponding ORC literature: R-245fa [24,25] and R-123 [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Repeated charge determination experiments are sometime required, which is neither environmentally friendly nor economical. It has been proved that a reasonable critical charge could also be calculated with an appropriate charge determination modeling, which significantly improves the analysis efficiency . In the optimum charge calculation, the single‐phase refrigerant part could easily be handled with its density and volumes of the section, while that of the two‐phase refrigeration in heat exchangers is somewhat difficult since it needs estimations with appropriate void fraction correlation models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that a reasonable critical charge could also be calculated with an appropriate charge determination modeling, which significantly improves the analysis efficiency. 17,18 In the optimum charge calculation, the single-phase refrigerant part could easily be handled with its density and volumes of the section, while that of the two-phase refrigeration in heat exchangers is somewhat difficult since it needs estimations with appropriate void fraction correlation models. Void fraction correlation FIGURE 1 A schematic of secondary loop air-conditioning heat pump system [Colour figure can be viewed at wileyonlinelibrary.com] models could be divided into four categories: homogeneous correlation, slip ratio correlations, K□h correlations, and drift flux correlation.…”
Section: Introductionmentioning
confidence: 99%